2022
DOI: 10.3390/cancers14246036
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics-Based Prediction of Future Portal Vein Tumor Infiltration in Patients with HCC—A Proof-of-Concept Study

Abstract: Portal vein infiltration (PVI) is a typical complication of HCC. Once diagnosed, it leads to classification as BCLC C with an enormous impact on patient management, as systemic therapies are henceforth recommended. Our aim was to investigate whether radiomics analysis using imaging at initial diagnosis can predict the occurrence of PVI in the course of disease. Between 2008 and 2018, we retrospectively identified 44 patients with HCC and an in-house, multiphase CT scan at initial diagnosis who presented withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Xun et al 13 combined clinical and radiomic-based characteristics to construct a model for predicting HCC microvascular invasion (MVI) and patient prognosis and the model demonstrated good detection efficiency. Stoehr et al 14 found that radiomics analysis using imaging at initial diagnosis might be a useful tool for identifying patients with HCC who are at risk for portal vein infiltration during follow-up, and that would benefit from closer monitoring. The 2 studies prove that radiomics analysis is useful for predicting both MVI and macrovascular invasion of HCC which determine the patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Xun et al 13 combined clinical and radiomic-based characteristics to construct a model for predicting HCC microvascular invasion (MVI) and patient prognosis and the model demonstrated good detection efficiency. Stoehr et al 14 found that radiomics analysis using imaging at initial diagnosis might be a useful tool for identifying patients with HCC who are at risk for portal vein infiltration during follow-up, and that would benefit from closer monitoring. The 2 studies prove that radiomics analysis is useful for predicting both MVI and macrovascular invasion of HCC which determine the patient's prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…An estimation model of walking age using five gait parameters was created by multiple regression analysis. The walking data of 97 participants were randomly divided into training data (80%, N = 78) and test data (20%, N = 19) 23 , 24 . Table 4 shows the characteristics of the training and test datasets.…”
Section: Methodsmentioning
confidence: 99%